'Just choose the easy option': students talk about alcohol use and social influence. (7th February 2016) - Hepworth, Julie; McVittie, Chris; Schofield, Toni; Lindsay, Jo; Leontini, Rose; Germov, John
Abstract : Previous research into young people's drinking behaviour has studied how social practices influence their actions and how they negotiate drinking-related identities. Here, adopting the perspective of discursive psychology we examine how, for young people, social influences are bound up with issues of drinking and of identity. We conducted 19 focus groups with undergraduate students in Australia aged between 18 and 24 years. Thematic analysis of participants' accounts for why they drink or do not drink was used to identify passages of talk that referred to social influence, paying particular attention to terms such as 'pressure' and 'choice'. These passages were then analysed in fine-grained detail, using discourse analysis, to study how participants accounted for social influence. Participants treated their behaviour as accountable and produced three forms of account that: (1) minimised the choice available to them, (2) explained drinking as culture and (3) described resisting peer pressure. They also negotiated gendered social dynamics related to drinking. These forms of account allowed the participants to avoid individual responsibility for drinking or not drinking. These findings demonstrate that the effects of social influence on young people's drinking behaviour cannot be assumed, as social influence itself becomes negotiable within local contexts of talk about drinking.